PREVENTION OF DIABETIC FOOT ULCERS IN VULNERABLE ADULT GROUPS IN THE COMMUNITY THROUGH THE JULAKWAKRI TOOLS INTERVENTION - Nursanti, Indah (Nurse and Holistic Care, 2025)
Background: This study is an application of Evidence-Based Nursing Practice in the prevention of diabetic foot ulcers (DFU) in vulnerable adult communities through the JULAKWAKRI intervention tools (seven steps of self-care foot care). Objective: To assess the effectiveness of JULAKWAKRI tools in preventing foot injuries in diabetic patients.  Methods: This quasi-experimental study with a pre- and post-test control design was conducted in the Harapan Mulya RW 4, 5, and 6 community areas in Kemayoran, Central Jakarta. The instruments used included the Spoken Knowledge in Low Literacy Diabetes (SKILLD) questionnaire, the Diabetes Empowerment Scale–Short Form (DES-SF), the Diabetes Problem-Solving Skills (DPSS) scale, and blood glucose measurements for glycemic control. Data were analyzed using the paired t-test to determine changes before and after the intervention. Results: The intervention significantly improved knowledge (MD: 28.44; p: 0.007), empowerment (MD: 16; p: 0.006), and problem-solving (MD: 34; p: 0.008). In addition, objective outcomes based on glycemic control also showed a significant decrease of up to 132.56 points (p: 0.008). Conclusion: DFU prevention is an essential component of empowering communities to become more independent and improving the health status of diabetic patients vulnerable to foot ulcers. The JULAKWAKWARI tools can be recommended as an effective intervention in community-based nursing practice.